Emerging Trends in Hybrid Additive and Subtractive Manufacturing - Manuel Ángel Rabalo; Amabel García; Eva María Rubio (Applied Sciences)
The great capability of additive manufacturing to produce parts with complex, even impossible to achieve, geometries through five-or-more-axis machining or other conventional processes opened a promising future decades ago. For its part, mature subtractive manufacturing presents problems of material waste, especially relevant in the case of superalloys used in fields such as aerospace. From the need to overcome the limitations of both and take advantage of their capabilities, the new paradigm of hybrid additive and subtractive manufacturing was born, which today is defined as a hybrid flow of subprocesses that interact with the part in the same machine. This paper presents a review of the emerging trends in additive–subtractive manufacturing over the last five years. This review has been carried out by applying an adaptation of the PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) methodology to the field of manufacturing engineering. Specifically, open access papers published in English between 2020 and 2024, collected in prestigious journals (classified as Q1 and Q2 within the ranking of their respective categories according to the Journal Citation Report), and peer-reviewed conference proceedings of recognized prestige have been selected. From the analysis of the selected articles, it is concluded that hybrid additive and subtractive manufacturing is especially focused on the aerospace field, using titanium and nickel alloys, combining processes among which DED (directed energy deposition) and milling stand out.